DAMPAK PEMBANGUNAN JALAN LINGKAR AMBARAWA TERHADAP PERKEMBANGAN UKM SERABI NGAMPIN AMBARAWA - Witjaksono Eko Hartoto; Tri Rinawati; Rita Meiriyanti; Diana Puspitasari (Jurnal Dinamika Sosial Budaya, 2017)
Construction of new road network ring, was actually giving an indirect impact on the socio-economic to the surrounding population. The existence of Ambarawa Ring Road is alleged to give effect to the business group pancake merchants who are members of the UKM Mekar Sari.The method used in this research is qualitative method with phenomenological approach. Researchers describe the research subjects are traders pancake incorporated in one business group SME Ngampin Ambarawa village called Mekar Sari totaling 40 people as actors who are the target of observation or informants in a study conducted by the researchers. In this study, the types and sources of data used are primary data and secondary data.Negative impacts to the ring road is a decrease in turnover of each of the traders pancake that is because the users prefer to go straight through the roundabout Ambarawa while the positive impact that arises in the presence of a ring road, traders are more willing to be creative that is willing to innovate products with try flavors and display products such as jackfruit, banana and sow meses cheese. It is intended to draw back buyers. This area actually has the potential and the need to touch or redirection location lots crossed by vehicles. They just need a lot of people know that they are still there, and what they contributed still feasible to provide a sensation with their typical food when passing on the street Ambarawa.